Scorpion Venom Causes Apoptosis by Increasing Reactive Oxygen Species and Cell Cycle Arrest in MDA-MB-231 and HCT-8 Cancer Cell Lines - Abdulrahman Khazim Al-Asmari PhD; Anvarbatcha Riyasdeen PhD; Mozaffarul Islam PhD (SAGE Publishing, 2018)
Objectives. The objective of this study was to examine the effect of scorpion venoms on cancer cell progression, apoptosis, and cell cycle arrest. Scorpion venoms are known to possess numerous bioactive compounds that act against cancer progression by inducing apoptosis. In this study, we have taken the venoms from the following 2 species of scorpion- Androctonus crassicauda and Leiurus quinquestriatus -and tested the anticancer properties of the venom against breast and colorectal cancer cell lines. Methods. Milking of scorpion venom and culturing the breast and colorectal cancer cell lines were done according to the standard procedure. The venom cytotoxicity was assessed by MTT methods, and the cellular and nuclear changes were studied with phase contrast and propidium iodide staining, respectively. The cell cycle arrest and accumulation of reactive oxygen species were analyzed on a Muse cell analyzer. Results. The venoms exerted cytotoxic effects on breast and colorectal cell lines in a dose- and time-dependent manner. Enhanced apoptotic cells, increase in reactive oxygen species, and cell cycle arrest were observed after challenging these cell lines with scorpion venoms. Conclusions. Scorpion venom induces apoptosis in breast and colorectal cell lines as reflected by the changes in the cell morphology and cell cycle studies. Furthermore, a high percentage of total reactive oxygen species as well as apoptotic cells also contribute to cell death as observed after venom treatments. To the best of authors' knowledge, this is the first scientific evidence demonstrating the induction of apoptosis and cell cycle arrest by these species of scorpion venoms.